Literature Review: Leadership Styles in Organizational and Cultural Contexts - Angelia, Christin (Jurnal Locus Penelitian dan Pengabdian, 2025)
Leadership is a fundamental factor in organizational effectiveness, whether in the public, educational, and business sectors. The eight articles reviewed in this paper examine various dimensions of leadership styles, ranging from transformational, transactional, charismatic, to the influence of cultural context. The results of the review show that transformational leadership styles consistently contribute positively to job satisfaction, performance, and organizational commitment, while laissez-faire styles tend to have a negative effect. In addition, national cultural factors, demographic diversity, gender, and communication are important mediators in leadership effectiveness. These studies underscore the need to develop leadership models that are more contextual, inclusive, and social justice-oriented in the era of globalization.